Interaction between charged nanoparticles and vesicles: coarse-grained molecular dynamics simulations. Issue 46 (15th November 2016) - Liu, Linying; Zhang, Jianhua; Zhao, Xiaowei; Mao, Zheng; Liu, Na; Zhang, Youyu; Liu, Qing Huo
Abstract : Interactions between charged nanoparticles and curved zwitterionic lipid vesicles with different surface charge densities ( ρ ): insertion, repulsion, adsorption, and penetration. Abstract : An enhanced understanding of the interactions between charged nanoparticles (CNPs) and a curved vesicle membrane may have important implications for the design of nanocarrier agents and drug delivery systems. In this work, coarse-grained molecular dynamics (CGMD) simulations of the CNPs with vesicles were performed to evaluate the effects of hydrophobicity, surface charge density and distribution on the curved vesicle membrane. The simulations reveal that there exist four distinct modes (insertion, repulsion, adhesion, and penetration) in the CNP–vesicle interaction. In contrast to previous studies on a planar membrane, the interactions of CNPs and a curved vesicle membrane show some novel properties. CNPs with low surface charge density (or neutral ones) can penetrate into the interior of the vesicle membrane more easily because of the increased membrane tension. The asymmetry between two leaflets of the membrane induces different interaction strengths of the negatively CNPs with the outer and inner leaflets. After penetration, the negatively CNPs prefer to stay close to the inner leaflet inside the vesicle where CNPs have stronger interactions with their surroundings. In the present work, we analyze the detailed mechanism of CNP's spontaneous penetration into vesicles, which is rarely mentioned in previous simulations. Moreover, we found that the negatively CNPs with the same surface charge density but different distribution result in different modes: the homogeneous mode is more likely to adsorb on the vesicle surface while the inhomogeneous mode tends to be more penetrable. In addition, the flip-flop phenomenon of the lipid membrane and the exchanging of water in or out of the vesicle were observed during penetration. Our results demonstrate that the electrostatic effect plays an essential role in the interaction between CNPs and vesicles. These findings suggest a way of controlling the CNP–vesicle interaction by coupling the hydrophobic properties, surface charge density and distribution of CNPs to enhance the probability of CNP's penetration into vesicles.